AdVEGF-All6A+ Preconditioning of Murine Ischemic Skin Flaps Is Comparable to Surgical Delay. Issue 8 (August 2015) - Gersch, Robert P.; Fourman, Mitchell S.; Phillips, Brett T.; Nasser, Ahmed; McClain, Steve A.; Khan, Sami U.; Dagum, Alexander B.; Bui, Duc T.
Abstract : Background: Surgical flap delay is commonly used in preconditioning reconstructive flaps to prevent necrosis. However, staged procedures are not ideal. Pharmacologic up-regulation of angiogenic and arteriogenic factors before flap elevation poses a nonsurgical approach to improve flap survival. Methods: Male Sprague Dawley rats were divided into control ( n = 16), surgical delay (Delay), AdNull, AdEgr-1, and AdVEGF ( n ≥ 9/group) groups. Delay rats had a 9 cm × 3 cm cranial based pedicle skin flap incised 10 days prior to elevation. Adenoviral groups received 28 intradermal injections (10 9 pu/animal total) throughout the distal two thirds of the flap 1 week prior to elevation. At postoperative day (POD) 0 flaps were elevated and silicone sheeting was placed between flap and wound bed. Perfusion analysis in arbitrary perfusion units of the ischemic middle third of the flap using laser Doppler imaging was conducted preoperatively and on POD 0, 3, and 7. Clinical and histopathologic assessments of the skin flaps were performed on POD 7. Results: AdVEGF (50.8 ± 10.9 APU) and AdEgr-1 (39.3 ± 10.6 APU) perfusion levels were significantly higher than controls (16.5 ± 4.2 APU) on POD 7. Delay models were equivalent to controls (25.9 ± 6.8 APU). AdVEGF and Delay animals showed significantly more viable surface area on POD 7 (14.4 ± 1.3 cm 2, P < 0.01 and 12.4 ± 1.2 cm 2, P < 0.05, respectively) compared with Controls (8.7 ± 0.7 cm 2 ). Conclusions: AdVEGF preconditioning resulted in flap survival comparable to surgical delay. Adenoviral preconditioning maintained perfusion levels postoperatively while surgical delay did not.